A new MDA approach based on BPM and SOA to improve software development process - Vidales,Miguel A. Sánchez (2008)
On Demand Business concept, from IBM, shows how to coordinate the transformation of enterprise organization and its technological infrastructure to bridge the gap between business and technology. This problem appears in most of the information systems. This concept is based on Service Oriented Architecture (SOA) to improve the connection between business services and software services. If companies can reach this On Demand Business environment they could improve the software development process by applying standards like Model Driven Architecture (MDA), to separate business logic from software and technological platforms, and Business Process Management (BPM) to define business processes as Computation Independent Models (CIM). In this article we propose a new MDA approach that combines BPM, SOA and the On Demand Business to improve the initial phase of the software development process. Starting on the creation of business processes models, classified like CIM, we can associate them to initial software models, based on software services, classified like Platform Independent Models (PIM).